A study on adequacy of Malaysian law governing drug adulteration: sildenafil / Shufira Muslim and Hasni Muniati Hassan - Muslim, Shufira; Hassan, Hasni Muniati (Faculty of Law, 2012)
As the adulteration of poison in Malaysia is still rampant, it causes a big impact on the government, enforcement agencies and users. It is a library-based research, however, semi structured interviews were also carried out which lead to a few findings of this study. The main Act that govern the manufacturing of poison is the Poisons Act 1952 (Act 366). Besides Act 366, the manufacturing of poison are also governed under the Sales of Drugs Act 1952 (Act 368) and the Control of Drugs and Cosmetics Regulation 1984. Subsequently, there is a role of the Good Manufacturing Practices that needs to be complied with. Apart from that, the regulatory being controlled by the Drug Control Authority, the Pharmacy Enforcement Division and the National Pharmaceutical Control Bureau including their roles in Pre and Post Marketing Surveillance, the use of Adulterated Database and also the new safety feature using distinct Hologram for registered products in Malaysia are clearly identified. Certain provisions in the Poison Act 1952, the Sales of Drugs Act 1952 and the Control of Drugs and Cosmetics Regulation 1984, need to be reviewed to accommodate with the current situation. The study examines and compares the existing laws in other country, namely the United State of America. It is recommended that stiffer penalty be imposed and to have a single specific Act that governs poison, for legal and administration improvement.